2021
DOI: 10.1007/978-3-030-68479-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Homes – A New Family Form – The Family Sociology Perspective

Abstract: In this chapter, we identify structural features of families with shared physical custody that differ from those of nuclear families or those of families where one parent has sole physical custody, and discuss the implications for family and kin relationships. We pay particular attention to the ways in which shared physical custody alters the gendered nature of parenting and kinship. We argue that the structural features of shared physical custody create distinct contexts for parent-child and sibling relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…A parent with shared physical custody is likely to have a greater insight into the child's social life via knowledge about his/her friends and their parents, and greater insight into the child's education as a result of meeting teachers when dropping off or picking up the child from pre-school or school, or by participating at parent-teacher meetings. These structural features of shared physical custody, affecting both the obligations of and relationships between family members, suggests we should view shared physical custody as a new family form that is different from both traditional two-parent families and traditional divorced families (Thomson and Turunen 2021). This type of post-separation living arrangement is also related to higher child wellbeing than living full-time with one parent (Nielsen 2011(Nielsen , 2014(Nielsen , 2018.…”
Section: Why Is Parent-child Distance Important?mentioning
confidence: 99%
“…A parent with shared physical custody is likely to have a greater insight into the child's social life via knowledge about his/her friends and their parents, and greater insight into the child's education as a result of meeting teachers when dropping off or picking up the child from pre-school or school, or by participating at parent-teacher meetings. These structural features of shared physical custody, affecting both the obligations of and relationships between family members, suggests we should view shared physical custody as a new family form that is different from both traditional two-parent families and traditional divorced families (Thomson and Turunen 2021). This type of post-separation living arrangement is also related to higher child wellbeing than living full-time with one parent (Nielsen 2011(Nielsen , 2014(Nielsen , 2018.…”
Section: Why Is Parent-child Distance Important?mentioning
confidence: 99%
“…As a result of more parents opting for shared residence after divorce, it has become more common for children to live approximately half of the time in the household of each biological parent (Bernardi & Mortelmans, 2021). This creates a distinct stepfamily form where multiple (step)parental figures can be (almost) equally active in the lives of children, making family relationships in multiple households more intertwined (Thomson & Turunen, 2021). Furthermore, research in the last decades has shown that nonresident biological parents are becoming more active in their children's lives (Westphal et al, 2014), along with nonresident stepparents becoming more present parental figures.…”
Section: Introductionmentioning
confidence: 99%